2003
DOI: 10.1097/01.mnm.0000084579.51410.69
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition improves cardiac fatty acid metabolism in patients with congestive heart failure

Abstract: This study aimed to examine whether angiotensin-converting enzyme (ACE) inhibition improved cardiac fatty acid metabolism in patients with congestive heart failure (CHF). Myocardial 123I-beta-methyl-iodophenylpentadecanoic acid (123I-BMIPP) imaging was performed in 25 patients with CHF and in 10 control subjects. Myocardial 123I-BMIPP images were obtained 30 min and 4 h after tracer injection. The heart-to-mediastinum (H/M) ratio of 123I-BMIPP uptake and the washout rate of 123I-BMIPP from the myocardium were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…9 The washout rate of BMIPP in the present case increased in accordance with the improvement in LV function after PTX, although it has been reported that the washout rate of BMIPP is enhanced in patients with heart failure. 18,24,25 The increase in the washout rate in the present case might correspond to improved transportation of BMIPP-CoA through the mitochondrial membrane affected by PTH, as the level of carnitine did not change after PTX, which also suggests that PTH played an important role in the LV dysfunction in the present case. The washout rate of 123 I-BMIPP might be a useful marker for estimating the effect of PTX on cardiac function.…”
Section: Metabolism Of the Myocardium And Pthsupporting
confidence: 51%
See 1 more Smart Citation
“…9 The washout rate of BMIPP in the present case increased in accordance with the improvement in LV function after PTX, although it has been reported that the washout rate of BMIPP is enhanced in patients with heart failure. 18,24,25 The increase in the washout rate in the present case might correspond to improved transportation of BMIPP-CoA through the mitochondrial membrane affected by PTH, as the level of carnitine did not change after PTX, which also suggests that PTH played an important role in the LV dysfunction in the present case. The washout rate of 123 I-BMIPP might be a useful marker for estimating the effect of PTX on cardiac function.…”
Section: Metabolism Of the Myocardium And Pthsupporting
confidence: 51%
“…The present case showed an increase in the H/M and washout of 123 I-BMIPP in accordance with improvement in congestive heart failure symptoms after PTX. Yamaguchi et al reported that the H/M decreased in patients with congestive heart failure, 18 and fatty acid uptake was reduced in an animal model of pacing-induced heart failure. 19 The increased H/M in the present case might indicate improved fatty acid uptake.…”
Section: Metabolism Of the Myocardium And Pthmentioning
confidence: 99%
“…Watanabe et al [12] reported a significant correlation between the effi cacy of the improvement in cardiac function induced by ACE-I and BMIPP indicators in chronic heart failure. Furthermore, Yamauchi et al [13] demonstrated a signifi cant improvement in the delayed H/M ratio and washout rate of BMIPP after ACE-I administration, and concluded that BMIPP is useful in evaluating the effi cacy of ACE-I. We previously examined the effi cacy of ES and SS of BMIPP for predicting the improvement in cardiac function as a result of beta-blocker therapy, and reported that ES and SS in patients with improved cardiac function are signifi cantly lower than in patients with no improvement [14].…”
Section: Usefulness Of Bmipp In the Evaluation Of Dcm Prognosismentioning
confidence: 97%
“…However, FA oxidation is easily impaired by various pathological factors leading to heart failure (HF). Iodine-123-labeled 15-(p-iodophenyl) -3-(R, S)-methylpentadecanoic acid ( 123 I-BMIPP) is a radioactive FA analog [2], and has been shown to be useful for evaluating the severity in patients with HF [3,4]. Myocardial uptake of 123 I-BMIPP was correlated with the grade of the New York Heart Association functional class [3].…”
mentioning
confidence: 99%
“…Iodine-123-labeled 15-(p-iodophenyl) -3-(R, S)-methylpentadecanoic acid ( 123 I-BMIPP) is a radioactive FA analog [2], and has been shown to be useful for evaluating the severity in patients with HF [3,4]. Myocardial uptake of 123 I-BMIPP was correlated with the grade of the New York Heart Association functional class [3]. Assessment of cardiac 123 I-BMIPP uptake was reported to be useful for predicting cardiac death in patients with chronic HF [5].…”
mentioning
confidence: 99%